2020
DOI: 10.1088/1361-6668/ab9aa2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of flux avalanches in type-II superconducting thin films under transient AC magnetic fields

Abstract: Flux avalanches induced from thermomagnetic instability are crucial challenges for the application of superconducting thin film devices. In this paper, flux avalanches in a type-II superconducting thin film exposed to a transient AC magnetic field are numerically simulated by solving the coupled nonlinear Maxwell's equations and the heat diffusion equation based on the fast Fourier transform (FFT) method. The dependence of the threshold magnetic field on the ambient temperature, film thickness and magnetic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
(110 reference statements)
1
8
0
Order By: Relevance
“…Jing et al numerically simulated the thermal-magnetic-mechanical properties in bulk and films. Their results enhanced researchers’ understanding of the relationship between cracks and magnetic flux motion [ 8 , 9 ]. Therefore, it is necessary to focus on studying stress distribution in the design of high-field superconducting magnets (including superconducting conductors) in order to reduce or avoid their performance degradation through optimized structure design.…”
Section: Basic Mechanical Problemsmentioning
confidence: 87%
“…Jing et al numerically simulated the thermal-magnetic-mechanical properties in bulk and films. Their results enhanced researchers’ understanding of the relationship between cracks and magnetic flux motion [ 8 , 9 ]. Therefore, it is necessary to focus on studying stress distribution in the design of high-field superconducting magnets (including superconducting conductors) in order to reduce or avoid their performance degradation through optimized structure design.…”
Section: Basic Mechanical Problemsmentioning
confidence: 87%
“…Motta et al experimentally observed the flux avalanches triggered by an AC field in a superconducting Nb film and revealed that the flux avalanches triggered at the increasing branch of the applied field can guide antiflux entry in the decreasing applied field [43,44]. This feature of flux avalanches under an AC field was then reproduced by Jing and Ainslie using numerical simulations [45]. However, there is also another interesting and unresolved question on the sensitivity of thermomagnetic instability in the superconducting film to the magnetic perturbation: namely, how the applied magnetic field affects the electromagnetic breakdown event if superimposing a small AC magnetic oscillation on a linearly increasing DC field.…”
Section: Introductionmentioning
confidence: 91%
“…Besides the above DC cases, where the applied field increases linearly with a constant ramp rate, the electromagnetic responses (e.g. critical current, AC loss, and thermomagnetic instability) of superconductors exposed to the AC field have been widely investigated [35][36][37][38][39][40][41][42][43][44][45]. Motta et al experimentally observed the flux avalanches triggered by an AC field in a superconducting Nb film and revealed that the flux avalanches triggered at the increasing branch of the applied field can guide antiflux entry in the decreasing applied field [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Some aspects of the appearance and behavior of avalanches in niobium films as a function of film thickness have been studied by us [9] and others [10][11][12], but the correlation between such thickness-dependent behavior and the thermal properties of the superconducting material and the film-substrate interface has not yet been studied experimentally. In this paper, we report an investigation of both temperature and film thickness dependence of the H th and l th in Nb films deposited on the glass substrates, and on the basis of the above theoretical model [3,4], we obtain the thermal conductivity, the film-to-substrate heat transfer coefficient or Kapitza thermal boundary conductance (TBC), and the critical current density of our films.…”
Section: Introductionmentioning
confidence: 99%